Measuring the effect of a mobile coronary care unit upon the community. Issue 4 (April 1979) - Vetter, N J; Pocock, S; Julian, D G
Abstract : A mobile coronary care unit working within a geographically defined area retrieved 20% of the estimated number of cases with myocardial infarction. These cases were similar to the population at risk in terms of age, sex, and previous history of ischaemic heart disease. Patients retrieved by the mobile unit had a lower overall case fatality ratio. This discrepancy was greater than could be explained by resuscitation or preventive treatment by the mobile unit teams. Reasons for this difference in mortality were explored. The benefits of the mobile coronary care unit were obvious in terms of the existing service but small in terms of the community. Any judgment on the effectiveness of a mobile unit must use both approaches to get a balanced view.